ECG Made Easy® - Luthra, A. Atul (Made Easy, 2020)
The aim of this book is to focus on the ECG Made Easy®. In an era of high-tech diagnostic modalities that include echocardiography and angiography as well as of sophisticated techniques of implantable devices such as stents, valves and pacemakers, introducing a book on ECG may sound somewhat primitive. This book consists of 28 chapters, which include nomenclature of ECG deflections, electrocardiographic leads, determination of electrical axis, determination of heart rate, abnormalities of the P wave, abnormalities of the T wave, abnormalities of PR interval, pauses during regular rhythm, normal regular rhythm with narrow QRS, fast irregular rhythm with bizarre QRS, slow irregular rhythm with narrow QRS etc. In the entire book, due emphasis has been laid on causation, mechanism, differential diagnosis and the management of classical electrographic entities and syndromes. This book ECG Made Easy has now been translated into several international languages is particularly gratifying. A concise handbook on ECG would be of enormous benefit to the greenhorns of cardiology (students and residents) as well as paramedic personnel (nurses and technicians).